2020
DOI: 10.1080/14737167.2020.1804873
|View full text |Cite
|
Sign up to set email alerts
|

Health equity and the usage of atypical antipsychotics within the Brazilian national health system: findings and implications

Abstract: Background: There is a need to evaluate the health equity of atypical antipsychotics users who obtain their medicines from the Brazilian National Health System (SUS) through the identification of key factors that influence their health status due to concerns with equity of care. Research design and methods:Cross-sectional study among patients attending state pharmacies in Brazil. Individuals were included if they used atypical antipsychotics, aged ≥18 years, and answered the EQ-5D-3L questionnaire. Sociodemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…SUS is the Brazilian public health system nationwide and serves all individuals, without depending on the individual's socio-economic status (SES), covering both complex and simple medical procedures as well as authorized medicines including high cost medicines. These medicines are provided free-of-charge provided that patients meet the agreed prescribing criteria every three months [31][32][33]. However, patients are free to purchase their medicines privately, either by paying out of pocket or through private health plans.…”
Section: Data Source Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…SUS is the Brazilian public health system nationwide and serves all individuals, without depending on the individual's socio-economic status (SES), covering both complex and simple medical procedures as well as authorized medicines including high cost medicines. These medicines are provided free-of-charge provided that patients meet the agreed prescribing criteria every three months [31][32][33]. However, patients are free to purchase their medicines privately, either by paying out of pocket or through private health plans.…”
Section: Data Source Study Design and Populationmentioning
confidence: 99%
“…In Brazil, the public health system [Sistema Único de Saúde (SUS)] provides both typical antipsychotics, i.e. chlorpromazine and haloperidol, in both oral and injectable presentations as well as oral atypical antipsychotics, clozapine, olanzapine, quetiapine, risperidone and ziprasidone, free of charge for patients with schizophrenia [31,32]. Previous studies conducted in Brazil among patients in the SUS reported that atypical antipsychotics were responsible for most of the direct medical expenditures in a cohort of eleven years follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation